2007
DOI: 10.1002/app.27095
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of liquid deproteinized natural rubber having epoxy group (LEDPNR)/poly (L‐lactide) blend

Abstract: Reaction after mixing of liquid epoxidized natural rubber/poly(L-lactide) blend was performed to enhance the compatibility of the blend. The liquid epoxidized natural rubber was prepared by epoxidation of deproteinized natural rubber with peracetic acid in latex stage followed by depolymerization with peroxide and propanal. The resulting liquid deproteinized natural rubber having epoxy group (LEDPNR) was mixed with poly(L-lactide) (PLLA) to investigate the compatibility of the blend through differential scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 21 publications
0
27
1
Order By: Relevance
“…A more recent objective has been to increase the bio-based content of these polymer blends. Among the main polymer families that have been blended with PLA, polyolefins [3][4][5][6][7], vinyl and vinylidene polymers [8,9] and copolymers [23][24][25], and elastomers and rubbers [10][11][12]26] can be extensively found in the research literature. 1 …”
Section: Pla/nonbiodegradable Polymer Blendsmentioning
confidence: 99%
See 3 more Smart Citations
“…A more recent objective has been to increase the bio-based content of these polymer blends. Among the main polymer families that have been blended with PLA, polyolefins [3][4][5][6][7], vinyl and vinylidene polymers [8,9] and copolymers [23][24][25], and elastomers and rubbers [10][11][12]26] can be extensively found in the research literature. 1 …”
Section: Pla/nonbiodegradable Polymer Blendsmentioning
confidence: 99%
“…proposed that epoxidized natural rubber (ENR), having higher reactivity and better mechanical properties than NR, could be a good candidate to toughen PLLA since compatibility between the polymer pairs could be generated via interaction of the epoxy group from the ENR and the ester group from PLLA [26]. However, the naturally occurring proteins of ENR may prohibit formation of ester linkages between epoxy and ester groups.…”
Section: Epoxidized Natural Rubber/pla Blends It Wasmentioning
confidence: 99%
See 2 more Smart Citations
“…As NR is an unsaturated polymer with a large number of double bonds in the backbones that are reactive, epoxidized natural rubber (ENR) can be prepared in latex stage by reacting natural rubber with peroxide [26] [27] forming epoxy groups of ENR that would improve the polarity of rubber and hence promoting compatibility with PLA. Nghia et al [28] investigated the compatibility of the ENR/PLA solution blend; they concluded that the reaction occurred between the epoxy groups of ENR and the ester groups of PLA. In this way, a new biomaterial based on PLA/ENR electrospun blends was obtained by electrospinning approach and the effect of ENR content on the blends was studied with the help of characterization techniques such as scanning electronic microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and dynamic mechanical analysis (DMA).…”
Section: Introductionmentioning
confidence: 99%